2021
DOI: 10.1093/bioinformatics/btab240
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental gene network rewiring at the second order within and across mammalian systems

Abstract: Motivation Genetic or epigenetic events can rewire molecular networks to induce extraordinary phenotypical divergences. Among the many network rewiring approaches, no model-free statistical methods can differentiate gene-gene pattern changes not attributed to marginal changes. This may obscure fundamental rewiring from superficial changes. Results Here we introduce a model-free Sharma-Song test to determine if patterns differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Further, comparing distributions of clinical diagnoses across clusters showed that clusters derived by GMM-baseline ( χ 2 (9) = 226.4, p < 0.001 ) have a more uniform distribution of clinical diagnoses than MTMderived clusters ( χ 2 (9) = 308.0, p < 0.001 ). Comparing between models (Table S5) showed significantly higher deviation of the joint distribution of cluster assignment and clinical diagnosis from the product of the marginals for MTM than GMM-baseline (Sharma-Song test for second-order differentials in contingency tables 33 , χ 2 (9) = 48.3, p < 0.001 ). These results suggest that MTM training on longitudinal rather than baseline data alone stratifies individuals more reliably to clusters of cognitive health based on future disease progression.…”
Section: Mtm Training On Trajectories Vs Baseline Data Alonementioning
confidence: 99%
“…Further, comparing distributions of clinical diagnoses across clusters showed that clusters derived by GMM-baseline ( χ 2 (9) = 226.4, p < 0.001 ) have a more uniform distribution of clinical diagnoses than MTMderived clusters ( χ 2 (9) = 308.0, p < 0.001 ). Comparing between models (Table S5) showed significantly higher deviation of the joint distribution of cluster assignment and clinical diagnosis from the product of the marginals for MTM than GMM-baseline (Sharma-Song test for second-order differentials in contingency tables 33 , χ 2 (9) = 48.3, p < 0.001 ). These results suggest that MTM training on longitudinal rather than baseline data alone stratifies individuals more reliably to clusters of cognitive health based on future disease progression.…”
Section: Mtm Training On Trajectories Vs Baseline Data Alonementioning
confidence: 99%